Design and implementation of an inventory management system in libraries using radio frequency identification technology - Mvoulabolo, Meryle K. (Vaal University of Technology, 2019)
Radio Frequency Identification Technology (RFID) technology is increasingly being used in multiple applications due to its low cost and ability to provide a high quality of identification. The cost benefit of RFID system is seen in the reduction in labor required to perform routine tasks such as inventory. With RFID, inventory-related tasks can be done in substantially less time compared to other commonly used auto-identification systems. Recent research has illustrated the application of RFID in multiple application scenarios. RFID can be used for real-time patient identification and monitoring in hospitals, but also for product expiration-date management in retail industries. Some enterprises in South Africa uses a combination of RFID technology and Internet of Things (IoT) to detect misplaced products and to detect low stock levels. Furthermore, RFID is also used for inventory management in libraries as discussed in this dissertation. In this dissertation, a combination of RFID and ZigBee technologies was used to reduce the time spent to perform inventory in libraries. An inventory management system was designed, simulated and built in order to count and locate books inside a library hence improving inventory process time in libraries. The overall results were satisfactory which lead to the achieving of the objectives set in this study.
M. Eng. (Department of Process Control and Computer Systems, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: RFID (Radio Frequency Identification Technology); Internet of Things; Inventory Management System; Libraries; Wireless sensor network; Dissertations, Academic -- South Africa.; Radio frequency identification systems.; Inventory control.; Libraries--Inventory control.; Internet of things.; Wireless sensor networks.; System design.